Encapsulating probiotics in novel resistant starch wall material for production of rice flour extrudates. (April 2021) - Ashwar, Bilal Ahmad; Gani, Asir; Gani, Adil; Ahmad, Mudasir; Shah, Asima
Abstract: Rice flour was substituted with RS4 microcapsules at 0%, 5%, 10%, 15% and 20% substitution levels to prepare functional extrudates. Pasting properties of rice flour -RS4 blends displayed significant (p ≤ 0.05) decreases in pasting properties with increasing RS4 content. The increase of RS4 content in flour resulted in the fall of both storage modulus (G′) and loss modulus (G″). The amylose content, RS content and water intake capacity of extrudates increased significantly with increasing RS4 content. Addition of RS4 microcapsules up to 20% did not affect the textural parameters of extrudates. Thermal transition temperatures of rice extrudates also increased with the percentage of increased RS4. SEM images of RS4-rice flour extrudate samples showed a more discontinuous structure with cracks and void spaces compared to control. FT-IR spectra revealed a new peak between 1244 and 1266 cm −1 in RS4 enriched extrudates which is attributed PO stretching in RS4. The survival of probiotics after extrusion demonstrated that RS4 microcapsules can be incorporated into the extrudates for preparation of functional foods. Addition of RS4 to rice extrudates up to 20% did not affect the overall acceptability of these products by consumers. Highlights: Rice flour was substituted with RS4 to prepare functional extruded product. Addition of RS4 up to 20% did not affect the textural parameters of extrudates. Thermal properties of extrudates increased when the increase in RS4. Survival of probiotics after processing reveals RS4 as a potential wall material.